Formation of size-dependent and conductive phase on lithium iron phosphate during carbon coating - Yulong Liu (Nature Portfolio, 2018)
Coating the active materials of interest with carbon is a widely employed way to boost the performance of lithium ion batteries. Here the authors show the formation of a conductive phase on LiFePO4 during carbon coating, which is size, annealing temperature and reduction atmosphere dependent.